An organoid biobank for childhood kidney cancers that captures disease and tissue heterogeneity - Camilla Calandrini (Nature Portfolio, 2020)
Pre-clinical cell culture models capturing the heterogeneity of childhood kidney tumours are limited. Here, the authors establish and characterise an organoid biobank of tumour and matched normal organoid cultures from over 50 children with different subtypes of kidney cancer.